Hubungan Pengetahuan Perawat dengan Pelaksanaan Patient Safety di Rumah Sakit: The Relationship Between Nurses' Knowledge with Implementation of Patient Safety in Hospitals - Safriliani Dwi Astuti; Feri Catur Yuliani; Yeni Rusyani (Universitas Ngudi Waluyo, 2026)
Quality of nursing care can be seen from the implementation of patient safety. One of the factors influencing patient safety implementation is nurses' knowledge, where knowledge is something acquired thru the learning process. This study aims to analyze the relationship between nurses' knowledge and the implementation of patient safety at Pati Islamic Hospital. The research type is descriptive correlational with a cross-sectional design. The population consists of all registered nurses in the inpatient wards, with 39 respondents selected using proportional sampling techniques. The data collection tool used a knowledge questionnaire, and implementation patient safety. The data analysis used the Chi-Square test. The research results showed that 41% of nurses had good knowledge and 59% had good patient safety implementation. The analysis test yielded a p-value of 0.000. Conclusion: There is a relationship between knowledge and nurses' implementation of patient safety. Further research is needed on other factors related to the implementation of patient safety.